PENERAPAN MEDIA PEMBELAJARAN MATH MOBILE LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SISWA KELAS IV - Nurul Nikmah; Ratri Rahayu; Nur Fajrie (PGSD Universitas Muria Kudus, 2020)
This study aims are to determine the improvement of mathematical problem solving skills with the application of math mobile learning media. The study was conducted in fourth grade of SD 1 PasuruhanKidul Kudus in the academic year 2018/2019 with the number of students 19.The research method used was the classroom action research method which lasted for two cycles, namely in cycle I and cycle II. Each cycle consists of planning, implementing, observing and reflecting. The independent variable in this study is math mobile learning media, while the dependent variable is the ability to solve math problems, student learning activities, and teacher teaching skills. Data collection techniques used in this study include observation, interviews, documentation and tests. This data analysis technique uses quantitative and qualitative data analysis.The results of this study indicate that the increase is, (1) The average mathematical problem solving ability of students with the percentage of classical completeness 68.42% (enough) in the first cycle to 94.73% (good) in the second cycle, (2) Activities student learning has increased with a value of 64.48 less (need guidance) in the first cycle and 76.72 (good) in the second cycle. (3) The percentage of teaching skills of teachers has increased by a percentage of 71% (enough) in the first cycle and 80.5% (good) in the second cycle. Based on the results of research carried out in class IV SD 1 PasuruhanKidul Kudus, it can be concluded that through math mobile learning media can improve the ability to solve mathematical problems in the surrounding material and flat area, student learning activities and teaching skills of teachers in teaching and learning.